Using spray-dried and encapsulated Nannochloropsis oculata biomasses in white spread - Polat, Derya Genc; Durmaz, Yasar; Konar, Nevzat; Pirouzian, Haniyeh Rasouli; Toker, Omer Said; Palabiyik, Ibrahim; Tasan, Murat (SPRINGER, 2022)
In this study, dried or encapsulated Nannochloropsis oculata microalgal biomass was used in spread samples (0.00-0.75 g (100 g)(-1) spread) as natural pigment source. Physicochemical properties, color stability, and rheological and sensory properties were investigated to assess the possibility of using microalgae biomass in white chocolate spread (WCS). The results showed that the chlorophyll-a amount increased while water activity, L*, a*, b*, and C* values significantly decreased upon incorporation of increased quantities of microalgae into WCS. Under accelerated shelf-life conditions for 35 days (25 degrees C/70% RH), Delta E values for all spread samples were determined as 0.05). The encapsulation application had advantages in terms of pigment amount and color stability. As a result, the use of N. oculata biomass may be an alternative ingredient to develop colored-spread products after drying or encapsulation by using spray-dryer method.
Keywords: Spread; Microalgae; Color; Nannochloropsis oculata; Pigment; PREBIOTIC MILK CHOCOLATE; SENSORY PROPERTIES; ALPHA-TOCOPHEROL; DARK CHOCOLATE; CHEWING GUM; FORMULATION; OPTIMIZATION; TEMPERATURE; PROFILES; Biotechnology & Applied Microbiology; Marine & Freshwater Biology